Management of Aceria litchii (Acari: Eriophyidae) on Litchi chinensis. (2018)
Litchi chinensis fruits are very popular in the international market. The erinose mite, Aceria litchii (Eriophyidae), a major pest of this crop, feeds on the leaves and on all parts of the plants forming erinea. The purpose of this review is to present the most common control methods and to propose integrated management techniques for L. chinensis production systems. A. litchii infestations were detected in Brazilian orchards in 2008. Chemical pesticides are currently the main control measure for this pest; however, the combination of biological, chemical and cultural methods are more promising in the long term. Controlling and preventing the erinose mite are key factors for reducing its spread and establishment